RNA modification mapping with JACUSA2 - Piechotta, Michael; Naarmann-de Vries, Isabel S.; Wang, Qi; Altmüller, Janine; Dieterich, Christoph (Genome biology, 2022)
Several high-throughput antibody-free methods for RNA modification detection from sequencing data have been developed. We present JACUSA2 as a versatile software solution and comprehensive analysis framework for RNA modification detection assays that are based on either the Illumina or Nanopore platform. Importantly, JACUSA2 can integrate information from multiple experiments, such as replicates and different conditions, and different library types, such as first- or second-strand cDNA libraries. We demonstrate its utility, showing analysis workflows for N6-methyladenosine (m6A) and pseudouridine (Ψ) detection on Illumina and Nanopore sequencing data sets. Our software and its R helper package are available as open source solutions.